Ñetonqataiqén, una canción «en desplazamiento» - Mansilla, Valentín (Universidad Nacional del Litoral, 2021)
Ethomusicological studies focused on the musical practices present in the current situation of indigenous people in Argentina (marked by on–going proceses and struggles for their visibilization) are thin on the academic ground. In this paper I think about the mocovi’s situation in Santa Fe province from a particular case of study: the «travel» of a song which was created by one of their leader (Alfredo Salteño) in order to be performed in their community meetings, and then was arranged by a professional musician (Luis Sartor) to be teached in rural schools. Through the analysis of four versions of the same song (three performed by Salteño and one by Sartor) I pretend elucidate their uses and transformations in order to draw up some answers to the underlying questions of this work: how impacts this song in mocoví’s visibility processes? What kind of actions are afforded by the new version? What features of this social movement and their aesthetic dimensions we can observe studying their «changing life»?